Deletion of a conserved noncoding sequence in Plzf intron leads to Plzf down-regulation in limb bud and polydactyly in the rat - Liska, Frantisek; Snajdr, Pavel; Sedová, Lucie; Seda, Ondrej; Chylíková, Blanka; Slámová, Petra; Krejcí, Eliska; Sedmera, David; Grim, Milos; Krenová, Drahomíra; Kren, Vladimír (Developmental dynamics, 2009)
Lx mutation in SHR.Lx rat manifests in homozygotes as hindlimb preaxial polydactyly. It was previously mapped to a chromosome 8 segment containing the Plzf gene. Plzf (promyelocytic leukemia zinc finger protein) influences limb development as a direct repressor of posterior HoxD genes. However, the Plzf coding sequence is intact in the Lx mutants. Using linkage mapping in F2 hybrids, we downsized the segment containing Lx to 155 kb and sequenced conserved noncoding elements (CNEs) inside. A 2,964-bp deletion in Plzf intron 2, never detected in control animals, is the only candidate for Lx. The deletion removes the most deeply conserved CNE in the 155-kb segment, suggesting a regulatory influence on Plzf expression. Correspondingly, using in situ hybridization and quantitative real-time polymerase chain reaction, we found a decrease of Plzf expression in Lx/Lx limb buds with concomitant anterior expansion of expression domains of its targets, Hoxd10-13 genes, in the absence of ectopic Sonic hedgehog expression. Upstream regulation of Plzf in limb buds is currently unknown. We present here the first candidate Plzf cis-regulatory sequence.
Keywords: DNA vazebné proteiny; Animals; polydaktylie; Base Sequence; Embryo, Mammalian; Gene Expression Regulation, Developmental; RNA, Untranslated; delece genu; Limb Buds; introny; končetinové pupeny; Polydactyly; Introns; Promyelocytic Leukemia Zinc Finger Protein; messenger RNA; Body Patterning; nekódující RNA; RNA, Messenger; protein promyelocytické leukemie s motivem zinkového prstu; Down-Regulation; Gene Deletion; konzervovaná sekvence; sekvence nukleotidů; DNA-Binding Proteins; krysa rodu Rattus; down regulace; zvířata; vývojová regulace genové exprese; embryo savčí; Rats; Conserved Sequence; rozvržení tělního plánu